Synergy between Common γ Chain Family Cytokines and IL-18 Potentiates Innate and Adaptive Pathways of NK Cell Activation - Nielsen, Carolyn M.; Wolf, Asia-Sophia; Goodier, Martin R.; Riley, Eleanor M. (Frontiers in Immunology, 2016)
Studies to develop cell-based therapies for cancer and other diseases have consistently shown that purified human natural killer (NK) cells secrete cytokines and kill target cells after in vitro culture with high concentrations of cytokines. However, these assays poorly reflect the conditions that are likely to prevail in vivo in the early stages of an infection and have been carried out in a wide variety of experimental systems, which has led to contradictions within the literature. We have conducted a detailed kinetic and dose-response analysis of human NK cell responses to low concentrations of IL-12, IL-15, IL-18, IL-21 and IFN-alpha, alone and in combination, and their potential to synergise with IL-2. We find that very low concentrations of both innate and adaptive common gamma chain cytokines synergise with equally low concentrations of IL-18 to drive rapid and potent NK cell CD25 and IFN-gamma expression; IL-18 and IL-2 reciprocally sustain CD25 and IL-18R alpha expression in a positive feedback loop; and IL-18 synergises with FcgRIII (CD16) signalling to augment antibody-dependent cellular cytotoxicity. These data indicate that NK cells can be rapidly activated by very low doses of innate cytokines and that the common gamma chain cytokines have overlapping but distinct functions in combination with IL-18. Importantly, synergy between multiple signalling pathways leading to rapid NK cell activation at very low cytokine concentrations has been overlooked in prior studies focusing on single cytokines or simple combinations. Moreover, although the precise common gamma chain cytokines available during primary and secondary infections may differ, their synergy with both IL-18 and antigen-antibody immune complexes underscores their contribution to NK cell activation during innate and adaptive responses.